Companies B: a diagnosis on its applicability - Rodríguez – Téllez, Fabián; Pacheco - Sánchez, Carlos Alberto (Universidad Francisco de Paula Santander, 2019)
The research encompasses an innovative way to support socially responsible companies through "System B", a strategic action that aims to be not only the best companies in the world but the best for the world. The main problem was defined as the scarcity of information about B companies in the city of Ocaña, which means that the benefit of their certification is not assured. The purpose of this research was to investigate the possible causes of the non-implementation of Companies B in Ocaña, as well as to determine their social and environmental responsibility practices. The research was quantitative and descriptive. We found zero certified companies and a high percentage of ignorance about the subject of study.